(untitled) (Bangladesh Journal of Agricultural Research, 2016)
A pot experiment was carried out in a venylhouse at Bangabandhu Sheikh Mujibur Rahman University during 2012 to investigate the growth, yield and yield contributing characters of ten selected soybean genotypes viz. Shohag, BARI Soybean-6, BARI Soybean-5, BD2331, BD2329, BD2336, BD 2340, BGM2093, G00015 and BGM2026 under drought stress and control conditions. Plant height, number of leaves, leaf area, shoot and root dry weight of all the genotypes were significantly affected by the stress. Among the genotypes Shohag, BARI Soybean-6 and BD2331 were found tolerant in relation to the growth under water stress conditions. The reduction in RGR values was more in the susceptible genotypes at the later stages of growth than in the tolerant genotypes. Seed yield of the genotypes was reduced from 42 to 68% due to drought (water) over non-stress. Susceptible genotypes showed greater reduction in seed yield than the tolerant genotypes. Bangladesh J. Agril. Res. 40(4): 537-550, December 2015